When Plasma Streams Tie up Equatorial Plasma Irregularities with Auroral Ones - Irina Zakharenkova; Iurii Cherniak (Space Weather)
Abstract We present a new pattern of storm‐induced ionospheric irregularities behavior at midlatitudes—poleward‐streaming plasma density depletions. Under disturbed conditions, they appear at North America low latitudes as a part of extended postsunset equatorial plasma bubbles, and further, they are streaming from low latitudes in a northwestward, poleward direction toward the main ionospheric trough and auroral irregularities zone. The poleward‐streaming plasma depletions represent a new phenomenon with the similar northwestward transportation path across the continental United States as storm‐enhanced density (SED) plumes. The channels of poleward‐streaming plasma depletions were stretched from low‐latitude base toward higher latitudes—they are found to occur for geomagnetic storms under specific combination of steady southward interplanetary magnetic field, subauroral polarization streams (SAPS) electric fields, and enhanced westward drifts at midlatitudes, resulting in northwestward plasma transportation equatorward of the SAPS region. The poleward‐streaming plasma depletions form an illusion of traveling ionospheric disturbances (TIDs) moving in a poleward, northwestward direction—this propagation direction is opposite to typical equatorward propagation of storm‐induced large‐scale TIDs generated in the auroral zone and propagated toward the equator. This phenomenon is accompanied by strong ionospheric irregularities that occurred over both edges of plasma depletion channel at midlatitudes. For two comparable geomagnetic storms, these poleward‐streaming plasma depletions persisted for several hours, posing a localized threat for GPS‐based positioning applications. Even moderate‐to‐intense storms (Dst minimum−145 nT) can promote such effects at midlatitudes.